Burns in Israel: Etiologic, Demographic, and Clinical trends—A 9-Year Updated Comprehensive Study, 2004–2010 versus 2011–2019 - Cohen-Manheim, Irit; Harats, Moti; Goldman, Sharon; Beylin, Dmitry; Haik, Josef; Bodas, Moran; Givon, Adi; Kornhaber, Rachel; Hayun, Yehiel; Cleary, Michelle; Hilewitz, Daniel; Tessone, Ariel; Israel Trauma Group (Seminars in Plastic Surgery, 2022)
Based on the Israeli National Trauma Registry (INTR) data, this study reports etiological, demographic, and clinical trends and includes all admissions to burn and trauma centers across Israel from 2011 to 2019 and compares these with 2004 to 2010 rates. From 2011 to 2019, 5,710 patients were admitted to burn centers across Israel. Children aged 0 to 1 years (25.9%), non-Jews (40.7%), and males (67.2%) remain the main groups of the burn casualties. Most of the casualties sustained 1 to 9% total body surface area (TBSA) burns with various depths. Scalds were less fatal than fire/flame-related casualties (<1 vs. 11.5%). Fewer surgical procedures were conducted for burns under 9% TBSA compared with greater TBSA. The percentage of TBSA and burn depth were found to be the most significant predictor of mortality among all age groups (>200 times increased risk with full-thickness burns >30% TBSA burn) and correlated with prolonged length of stay (>7 days).
Keywords: burns; etiology; Israel; risk groups; trauma registry